EXPLAINING ELECTORAL VICTORY THROUGH SOCIAL CAPITAL: A CASE STUDY OF A FORMER VILLAGE HEAD IN THE 2024 TEMANGGUNG LOCAL ELECTION, INDONESIA - Mukhamad Busro Asmuni; Gema Pertiwi; Hendika Dwinanda Wicaksana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The 2024 Temanggung Regency Regional Head Election (Pilkada) presented a compelling political phenomenon, wherein a former village head successfully triumphed over two incumbent candidates. This study aims to analyze the role and mechanisms of utilizing social capital in Agus Setyawan’s victory in the 2024 Temanggung Election. This research employs a descriptive qualitative approach, utilizing a social capital analytical framework encompassing three primary dimensions: trust, social networks, and norms of reciprocity. Data collection is assumed through literature reviews, media analysis, and the candidate's track record.The findings indicate that the candidate's victory was deeply rooted in the social capital accumulated during his 16-year tenure as the Village Head of Campurejo. First, the trust dimension was established through an empirical track record in transforming human resources within his village, including reducing early marriage rates and advancing education. Second, the expansion of social networks was executed effectively by capitalizing on farmer groups, cultural arts associations (kuda lumping), inter-village head solidarity, and supported by structural political networks. Third, norms of reciprocity were fostered through a populist and grassroots approach that positioned the candidate as an equal to the common citizenry, thereby generating solid voter loyalty.In conclusion, the conversion of communal social capital and grassroots support proved capable of dismantling the political hegemony of incumbents. The phenomenon of the 2024 Temanggung Election reaffirms that a proven track record and social proximity at the village level can serve as a superior political modality compared to mere elite popularity.